2015
DOI: 10.1016/j.ebiom.2015.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Do We Know Why We Make Errors in Morphological Diagnosis? An Analysis of Approach and Decision-Making in Haematological Morphology

Abstract: SummaryBackgroundThe laboratory interpretation of blood film morphology is frequently a rapid, accurate, and cost-effective final-stage of blood count analysis. However, the interpretation of findings often rests with a single individual, and errors can carry significant impact. Cell identification and classification skills are well supported by existing resources, but the contribution and importance of other skills are less well understood.MethodsThe UK external quality assurance group in haematology (UK NEQA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 27 publications
(29 reference statements)
1
24
1
Order By: Relevance
“…Finally, in contrast to other results previously published, 4,5 in reactive specimens our participants showed a great concordance with respect to the RR. In the two reactive surveys, most of the laboratories recognized reactive lymphocytes in PBS, considering almost all of them an infectious mononucleosis as the corresponding diagnosis.…”
Section: Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…Finally, in contrast to other results previously published, 4,5 in reactive specimens our participants showed a great concordance with respect to the RR. In the two reactive surveys, most of the laboratories recognized reactive lymphocytes in PBS, considering almost all of them an infectious mononucleosis as the corresponding diagnosis.…”
Section: Discussioncontrasting
confidence: 84%
“…The role of the PBS review in the diagnosis of lymphoma with abnormal lymphoid cells circulating in blood is to provide the first morphological orientation of the lymphoid neoplasm and to suggest which immunophenotyping or molecular analysis tests should be performed. Challenges in reporting whether a smear containing lymphocytes is associated with a reactive or neoplastic disease were highlighted previously by van der Meer et al 3 In addition, previous quality assurance control surveys showed that neoplastic misclassification of reactive lymphocytes occurs in 10 to 26% of cases 4,5 . On the other hand, two proficiency testing surveys revealed that a total of 21% of neoplastic cases were assigned as reactive 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency of morphological skills has been compounded further by the fact that senior haematologists with a major interest in this area are few and far between, making it difficult to motivate trainees to develop such a future interest. Maintenance of morphological skills is of crucial importance (Hamilton et al , ; Brereton et al , ). In the future a lack of skilled trainers may necessitate the increasing use of digital aids (Brereton & Burthem, ).…”
Section: Professional and Human Resources Challengesmentioning
confidence: 99%
“…According to quality assurance control surveys from Canada and the UK, neoplastic misclassification of reactive specimens occurs in 10-26% of cases (Brereton et al, 2015;Johnston et al, 2016) while up to 21% of neoplastic cases are assigned as reactive (Johnston et al, 2016), highlighting the need for improvement. Evaluation of the leucocyte subpopulation using DXH800 (Beckman Coulter, Miami, FL) analysers yields cell population data (CPD) with information on volume, conductivity (mean population values and SD) and 10 different scatter measures (Briggs, 2009;Bain, 2015).…”
Section: Machine Learning Algorithms For Accurate Differential Diagnomentioning
confidence: 99%